PELAYANAN PASTORAL HOLISTIK PADA RUMAH LANSIA GRIYA ADIYUSWA GIRI PRASANTI - Aguswanto, Johnny; Rogo Yuono, Yusup; Suwiknyo Tyas Mahendro, Joko (Sekolah Tinggi Teologi Sangkakala & Sekolah Tinggi Jemaat Kristus Indonesia, 2023)
The elderly home for some elders can be their last terminal before leaving this world. Services in the elderly's home should be a comprehensive service in addition to spiritual services to prepare the elderly to reach the end of life in this world. The concept of holistic spiritual services for the elderly is expected to improve services for the elderly which include health, psychological, recreational and other togetherness activities so that they can make the elderly feel comfortable even though they have to be separated from their old family and community. The research approach used is descriptive qualitative method through literature search of related matters. By understanding the parts of service for the elderly as a whole, it is hoped that spiritual service will become the main thing in implementing holistic services that will make the elderly find their identity as spirit beings who have a relationship with God as the owner of this life so that they will be ready and enjoy the rest. their age by remaining passionate and continuing to work according to their respective abilities and talents. Holistic pastoral care for the elderly will increase their passion to enjoy the rest of their lives in God's grace and still be able to contribute to the community where they are placed.